(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
The concept of learning styles has gained significant attention in educational research and practice over the past few decades. This article explores the various learning styles and approaches to studying, examining how individuals acquire, process, and retain information differently. It discusses the implications of these differences for educational settings and highlights the importance of adapting teaching methods to accommodate diverse learning preferences. A review of relevant research illustrates the relationship between learning styles and academic performance, ultimately advocating for a more tailored approach to education that considers individual differences.